Applications of ultrafast spectroscopy to sunscreen development, from first principles to complex mixtures. Issue 2 (3rd April 2019) - Holt, Emily L.; Stavros, Vasilios G.
ABSTRACT: Sunscreen formulations have been developed to provide an artificial protective barrier against the deleterious effects of overexposure to ultraviolet (UV) radiation in humans. Ultrafast pump-probe spectroscopy techniques have been an invaluable tool in recent years for determining the photochemistry of active ingredients in sunscreen formulations, predominantly UV filters, in both the gas- and solution-phases. These measurements have enabled the elucidation of molecular relaxation pathways and photoprotection mechanisms, which are in turn insightful for assessing a filter's photostability and suitability for sunscreen use. In this review, we discuss the benefits of a bottom-up approach: the progression from the study of UV filters for sunscreens in vacuum, away from the influences of any solvent; in solution, to investigate the relaxation pathways of potential sunscreen filters in closer to real-life conditions, whilst exploring the merits of selective functionalisation to improve their characteristics; and beyond, to current advances that are mimicking the application of sunscreen formulations to the surface of the skin.